Exploring the prevalence of birth defects of the gastrointestinal tract in newborns: A Six-year analysis in Bogotá, Colombia - Catalina Correa; Sandra Pastrán; María Camila León-Sanabria; María Paula Aguilera-Pena; José Nieto; Ana María Urueña-S fgerrano; Ignacio Zarante (Elsevier, 2023)
Background: Birth defects (BD) occur in 3-6 % of live births (LB) and constitute significant morbimortality and disability. Some BD of the gastrointestinal (GI) tract requires surgical interventions during the first days of life. Knowing the prevalence in different city areas could guide decision-makers in developing public policies that guarantee timely attention. This study aims to determine the prevalence of 7 GI defects in LB in Bogotá, Colombia, and to explore factors related to their occurrence. Methods: We conducted an analytical cross-sectional observational study based on data from the BD database of the Public Health Surveillance System (PHSS) of Bogotá between 2015 and 2021, using all available records where BD of the GI tract was reported. We performed descriptive analyses in Jamovi and correlation analyses in SPSS. Results: We included 869 cases in the study. GI defects occurred more frequently in males (50.5 %). Esophageal atresia was the BD most frequently reported (25.9 %), followed by gastroschisis and anorectal malformation (19 %). GI defects are more frequent in the city's center-east area of Bogota. The prevalence of GI defects in Bogota during the period studied was 14.2 per 10,000 LB. Of the LB with GI defects, 93.8 % had low socioeconomic status. Conclusions: The results of this study point to the importance of centralizing neonatal surgical care services for these pathologies in the sub-network that serves this population. Prenatal care, housing conditions, and substance use in the home were related to a higher prevalence of GI defects.